2023
DOI: 10.3390/md21030160
|View full text |Cite
|
Sign up to set email alerts
|

Potential Activity of Arthrospira platensis as Antioxidant, Cytotoxic and Antifungal against Some Skin Diseases: Topical Cream Application

Abstract: This research evaluated the antifungal effectiveness of Arthrospira platensis ethanol, methanol, ethyl acetate and acetone extracts against the tested pathogenic fungi (Candida albicans, Trichophyton rubrum and Malassezia furfur). Antioxidant and cytotoxicity effectiveness of A. platensis extracts against four distinct cell lines were also assessed. Methanol extract of A. platensis exhibited the highest inhibition zones against Candida albicans as measured by the well diffusion method. A transmission electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The high antioxidant activity of the MeOH extract could also contribute to the wound healing effect. Alkaloids, phytol, fatty acids hydrocarbons, phenolics and phthalates were found in the extract [134].…”
Section: In Vivo Antimicrobial Activitymentioning
confidence: 97%
“…The high antioxidant activity of the MeOH extract could also contribute to the wound healing effect. Alkaloids, phytol, fatty acids hydrocarbons, phenolics and phthalates were found in the extract [134].…”
Section: In Vivo Antimicrobial Activitymentioning
confidence: 97%
“…There is a lot of interest in screening beneficial medications derived from marine algae because they contain biomolecules, such as vitamins, polysaccharides, peptides, pigments, lipids, minerals, and proteins. They perform a variety of biological processes, such as antimicrobial (Gheda et al, 2013;Gheda et al, 2023a), anti-inflammatory, antioxidant (Ismail et al, 2019;Ismail et al, 2020;Gheda et al, 2021;Gheda et al, 2023b;Abo-Shady et al, 2023) and anticancer activities (Gheda et al, 2018).…”
Section: Et Al 2023)mentioning
confidence: 99%
“…Previous studies have also demonstrated a biological action of spirulina. For example, ethanolic and methanolic extracts have been shown to be effective as antifungals, and both cytotoxic and antioxidant [13,14]. Synthetic antioxidants are generally dangerous for humans if used long-term, so a natural antioxidant source that can reduce or prevent cellular damage caused by oxidative stress may be crucial for the prevention of diseases such as cancer [15].…”
Section: Introductionmentioning
confidence: 99%